A deep eutectic solvent-based extraction method for fast determination of Hg in marine fish samples by cold vapor atomic absorption spectrometry. Issue 39 (25th September 2017) - Rastegarifard, Farzaneh; Ghanemi, Kamal; Fallah-Mehrjardi, Mehdi
Abstract : The process of dissolution of marine fish samples in DES followed by a fast (∼5 s) and complete digestion in nitric acid for determination of Hg. Abstract : An efficient sample extraction method for determination of total Hg in fish samples was developed. The method is based on the complete dissolution of samples in a deep eutectic solvent (DES). Among the DESs considered, choline chloride–oxalic acid was the best, dissolving samples completely without additional microwave or pressure processing. After adding 7 mol L −1 HNO3 or higher, the sample was digested very quickly (∼5 s), and a residue-free and clear solution was obtained. Since there was no need for further steps such as centrifugation and filtration, the risk of the elemental contamination was greatly reduced. The Hg content of each sample was determined by cold vapor atomic absorption spectrometry. Under optimized conditions, the Hg extraction efficiencies of the spiked samples were in the range 94.5–97.0%. The precisions based on relative standard deviations for five successive replications spiked at 1.0 and 5.0 μg g −1 were 2.0% and 5.5%, respectively. The limit of detection of the method was 0.03 μg g −1 ( n = 8). Under optimized conditions, an excellent agreement between the obtained results and the certified values was observed. For comparison, different fish tissues (muscle and liver) were analyzed by both the proposed method and a conventional acid digestion method. Besides the high recoveries, our method was more rapid, energy saving, and environmentally friendly.